Indikacije za odstranitev modrostnih zob s stališča maksilofacialnega kirurga - Žerdoner, Danijel (Zdravniški vestnik, 2005)
Background. The removal of third molar is a problem which confronts many dentists and maxillofacial surgeons worldwide must confront. Also, the opinionabout indications and time of their removal differs. Methods. In the article the author suggests the removal of third molars by indications which he thoroughly analyzes. Conclusions. Based on our experience (6729) in last three years it is our opinion that third molar removal has few postoperative complications when indications are correctly considered and the judgment aboutremoval is established. Thus we can avoid unnecessary postoperative doubts about unfounded removal.
Keywords: kirurško zdravljenje; Kočnik tretji; modrostni zobje; Molar, Third; Tooth Extraction; zobje; Zobna ekstrakcija